Topological study of the H3++ molecular system: H3++ as a cornerstone for building molecules during the Big Bang. (18th October 2018) - Mukherjee, Bijit; Mukhopadhyay, Debasis; Adhikari, Satrajit; Baer, Michael
ABSTRACT: The present study is devoted to the possibility that tri-atomic molecules were formed during or shortly after the Big Bang. For this purpose, we consider the ordinary H3 + and H3 molecular systems and the primitive tri-atomic molecular system, H3 ++, which, as is shown, behaves differently. The study is carried out by comparing the topological features of these systems as they are reflected through their non-adiabatic coupling terms. Although H3 ++ is not known to exist as a molecule, we found that it behaves as such at intermediate distances. However, this illusion breaks down as its asymptotic region is reached. Our study indicates that whereas H3 + and H3 dissociate smoothly, the H3 ++ does not seem to do so. Nevertheless, the fact that H3 ++ is capable of living as a molecule on borrowed time enables it to catch an electron and form a molecule via the reaction H3 ++ + e → H3 + that may dissociate properly: Thus, the two unique features acquired by H3 ++, namely, that it is the most primitive system formed by three protons and one electron and topologically, still remain for an instant a molecule, may make it the sole candidate for becoming the cornerstone for creating the molecules. GRAPHICAL ABSTRACT: